2022
DOI: 10.1093/ckj/sfac206
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of real-world data to estimate chronic kidney disease prevalence and staging in an unselected population

Abstract: Chronic kidney disease (CKD) represents a global public health burden, but its true prevalence is not fully characterized in the majority of countries. We studied the CKD prevalence in adult users of the primary, secondary and tertiary healthcare units of an integrated health region of the north of Portugal (n = 136 993; representing approximately 90% of the region adult population). Of them, 45 983 (33.6%) had at least two eGFR assessments and 30 534 (22.2%) had at least two urinary albumin creatinine ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Chronic kidney diseases (CKD) have become a global public health issue, affecting more than 200 million people worldwide [ 117 ]. Chronic kidney disease is a common term used to describe different disorders that permanently affect the structure and function of the kidneys for over a period of 3 months [ 118 ]. This can be diagnosed when the abnormalities in the kidney or glomerular filtration rate are lower than 60 ml/min/1.73 m 2 and albuminuria is characterised by an albumin to creatinine ratio above 30 mg/g [ 119 ].…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%
“…Chronic kidney diseases (CKD) have become a global public health issue, affecting more than 200 million people worldwide [ 117 ]. Chronic kidney disease is a common term used to describe different disorders that permanently affect the structure and function of the kidneys for over a period of 3 months [ 118 ]. This can be diagnosed when the abnormalities in the kidney or glomerular filtration rate are lower than 60 ml/min/1.73 m 2 and albuminuria is characterised by an albumin to creatinine ratio above 30 mg/g [ 119 ].…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%
“…Ten years later, the RENA study demonstrated a global CKD prevalence in Portugal of 20.9%, this time considering stages 1 to 5, with the highest prevalence found in the central region of Portugal (25%) and the lowest (12%) in Madeira Island [ 8 ]. More recently, a study in the north region of Portugal estimated a CKD prevalence (stages 1 to 5) of 9.8% [ 9 ]. In fact, there is an irregular distribution of CKD prevalence in Portugal, but there are also significant differences across these studies that might make comparisons difficult, as mentioned in Table 1 .…”
Section: Editorialmentioning
confidence: 99%
“…Overall in Europe, we are 10% of the population with CKD, amounting to >800 million individuals [8]. In Portugal, the adult population is about 9 million, and 10% of this population (90 thousand) have DRC [9].…”
Section: Introductionmentioning
confidence: 99%